Penerapan Pajak Pertambahan Nilai (PPN) pada PT. Gelael Indotim Makassar (Studi Kasus) - Saleh, Andi Mulia (Patria Artha University, 2018)
This study aims to determine the suitability of the application of Value Added Tax (PPN) to PT. Galela Indotim Makassar with Law Number 42 of 2009 concerning Value Added Tax (VAT). Based on the results of research conducted shows that the application of Value Added Tax (VAT) at PT. Makassar Gelael Indotim has been compliant according to Law Number 42 of 2009